Model of Purchase Impulsive Behavior of Online Consumers: Case in Indonesia - Ratih Hurriyati, Ana A, Asnul Dahar Minghat , Thospon Sangswang (International Journal of Advanced Science and Technology, 2020)
The purpose of this study is a visual appeal that affects the perceive enjoyment and clarify the role of purchase intension factors in seeing the increase in on-line impulsive purchases in Indonesia. This research was conducted on 400 respondents who shop at the four largest on-line stores in Indonesia. The research method used is descriptive verification through quantitative approaches. The data analysis technique used in this study was path analysis using Amos Version 20 software. The results showed that Indonesian consumers tend to have impulsive nature when shopping online. Planning to buy something is still done by consumers before making a purchase, but because of the offers and programs conducted by on-line stores, consumers can be tempted so that an impulsive purchase occurs. The conveniences provided on-line shopping such as practical, saving time, saving energy, further strengthens the tendency of consumers to buy impulsively. The fact that supports this argument is the increasing number of Internet users in Indonesia to remote areas.